The use of plants to improve indoor air quality in small office space - Ghazali, Aini Jasmin; Mohamed, Noorizan; Maulan, Suhardi; Abd. Ghani, Murad; K., Ina (Universiti Putra Malaysia Press, 2012)

(untitled)
Exposure to volatile organic compounds (VOC) can cause a series of effects towards human health. VOC is also associated with Sick Building Syndrome and other building related illnesses. Common materials found in every home and place of business may cause elevated exposure to toxic chemicals. The aim of this study was to examine the best indoor plants that could be used to improve indoor air quality in a small office space. In this study, the concentration of VOC inside a room was monitored before and after the test, using Aeroquol Model S500 VOC Gas Detector and by using oil-based paint painted on a panel measuring 0.05 x 0.05 m in order to create a minimum of 3ppm of VOC. Three types of tropical indoor plants were used in this study; Nephrolepis exaltata, Rhapis excelsa and Dracaena fragrans. Data were monitored for eight hours at 10 minutes interval. The results showed no significant differences between the number of pots and the type of plants used in reducing VOC content in the real room environment. This was probably due to several factors, such as the interference of outside air and the condition of the experimental room. This experiment suggests that further experiments should be carried out in a controlled environment to improve our knowledge of how indoor plants can improve indoor air quality, and thus improve human health and well-being.